PENGARUH KUALITAS PRODUK MINUMAN KOPI TERHADAP KEPUASAN KONSUMEN DI LUAR GARIS TIBAN KOTA BATAM - Aidil Alvaridzi; Dailami (Puslitabmas Batam Tourism Polytecnic, 2023)
A food and beverage business in a coffee shop especially for satisfaction requires the quality of a drink, the writer needs to do an evaluation to find out if the drink menu is suitable for consumption and served the best for consumers. This study aims to determine the advantages and popularity of a drink by relying on the quality of the coffee from a barista when serving various flavors of the appropriateness of the drink to guests. And research is carried out by observing other things done by Baristas, such as paying attention to the tools and materials to be used as well as several methods carried out by baristas such as calibrating coffee machines, calibrating coffee beans, making ingredients, performance and cleanliness of baristas. Data processing with quantitative data as a support and descriptive approach, observation, interviews, documentation and distribution of questionnaires as a data collection technique carried Luar Garis Tiban The samples obtained in this study used the slovin formula